2022
DOI: 10.1017/9781108887304
|View full text |Cite
|
Sign up to set email alerts
|

Digital Technology, Politics, and Policy-Making

Abstract: This element shows, based on a review of the literature, how digital technology has affected liberal democracies with a focus on three key aspects of democratic politics: political communication, political participation, and policy-making. The impact of digital technology permeates the entire political process, affecting the flow of information among citizen and political actors, the connection between the mass public and political elites, and the development of policy responses to societal problems. This elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 210 publications
0
4
0
Order By: Relevance
“…The lack of technological literacy among legislators can lead to a reliance on industry experts for guidance, which, while necessary, risks creating regulations that favor indus try interests over public welfare. [55] observed that the technology sector's influence on policymaking can lead to regulatory frameworks that are more reflective of industry priorities than societal needs, underscoring the importance of technological expertise within regulatory bodies themselves. TECHNOLOGY AUDIT AND PRODUCTION RESERVES -№ 2/4(76), 2024…”
Section: «The Rapid Advancement Of Digital Technologies Often Outpace...mentioning
confidence: 99%
“…The lack of technological literacy among legislators can lead to a reliance on industry experts for guidance, which, while necessary, risks creating regulations that favor indus try interests over public welfare. [55] observed that the technology sector's influence on policymaking can lead to regulatory frameworks that are more reflective of industry priorities than societal needs, underscoring the importance of technological expertise within regulatory bodies themselves. TECHNOLOGY AUDIT AND PRODUCTION RESERVES -№ 2/4(76), 2024…”
Section: «The Rapid Advancement Of Digital Technologies Often Outpace...mentioning
confidence: 99%
“…Finally current discussion exercises tend to deliberately avoid substantive disagreement. While the intuition to steer clear of division is understandable, citizens often encounter polarizing messages from the media, political campaigns or from other citizens in online environments [19,20,[28][29][30], and it is in these contexts that polarized thinking becomes activated [31]. Thus, interventions to polarization ideally work in an environment that gives free rein to the issue disagreement that that partly drives inter-partisan animosity [32,33].…”
Section: Mainmentioning
confidence: 99%
“…It affects how citizens form political opinions, participate in politics, and interact with the state. The ambivalent effects of social media on democracy and the innovative tools, such as e-voting, e-collecting, and voting advice applications, that digital technologies enable have been prominently debated (Gilardi, 2022;Linder, 2022). In comparison to these topics, e-government -the digitization of administrative processes to improve service delivery and information exchange between governments and their stakeholders (Pleger & Mertes, 2022) -often receives less attention despite its potential to realize immediate benefits for citizens.…”
Section: Introductionmentioning
confidence: 99%